Efficacy of aggressive hydration with normal saline versus lactated Ringer’s solution for the prevention of post-ERCP pancreatitis in high-risk patients: a randomized controlled trial - Patel, Rupal; Bertran-Rodriguez, Carlos; Kumar, Ambuj; Brady, Patrick; Gomez-Esquivel, Rene; Changela, Kinesh; Niknam, Negar; Taunk, Pushpak (Endoscopy International Open, 2022)
Background and study aims Post-ERCP pancreatitis (PEP) is a common adverse event in high-risk patients. Current intervention known to reduce the incidence and severity of PEP include pancreatic duct stent placement, nonsteroidal anti-inflammatory drugs per rectum, and intravenous (IV) fluids. We compared aggressive normal saline (NS) vs aggressive lactated Ringer’s (LR) infusion for the prevention of PEP in high-risk patients undergoing ERCP.Patients and methods Patients were randomized to receive either an aggressive infusion of NS or LR. The infusion was started at a rate of 3 mL/kg/hr and continued throughout the ERCP procedure. A 20 mL/kg bolus was given at the end of the procedure, then continued at a rate of 3 mL/kg/hr.Results A total of 136 patients were included in our analysis. The incidence of PEP was 4 % (3/72 patients) in the LR group versus 11 % (7/64 patients) in the NS group resulting in a relative risk (RR) of 0.38 (95 % confidence interval [CI] 0.10 to 1.42; P = 0.19). The relative risk reduction (RRR) was 0.62 (95 % CI –0.41 to 0.90) along with an absolute risk reduction (ARR) of 0.07 (95 % CI –0.025 to 0.17) and an number needed to treat of 15 (95 % CI –41 to 6).Conclusions To our knowledge, this is the first study comparing aggressive IV NS to aggressive IV LR in high-risk patients. The incidence of PEP was lower in the group receiving an aggressive LR infusion (4 %) compared to NS infusion (11 %). However, the difference was not statistically significant likely due to poor accrual thereby impacting the power of the study.